PROSPEK PENGEMBANGAN INOVASI TEKNOLOGI BAWANG MERAH DI LAHAN SUB OPTIMAL (LAHAN PASIR) DALAM UPAYA PENINGKATAN PENDAPATAN PETANI - Endang Iriani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
Onion seed that has a certain quality ( good seed ) is a rare commodity and has not fulfill the needs of the farmers . The availability of seeds until August 2009 is still 19,770 tons consist of 13,400 tons of domestic seed and 6,370 tons imported seed, or there is only 20 % of 150 tons required. Purworejo is a district that has a potential coastal area that can be used for onion farming which is now being developed. One of the problems is the difficulty to got seed varieties due to lack of seed onion varieties especially on the land with sand. Therefore, it is necessary to build institutional seeding and distribution network to strengthen seed systems and the effectiveness of the distribution of onion for sub optimal land (land with sand). The prospects for the development of horticulture in the southern coastal area of Purworejo district is very potential, as long as the commodities give enough benefit. The results of the application of technology in onion farming on land with sand is good and got a positive response from the farmers. Judging from the trend of adoption, 35 % of respondents would seek for onion farming and cultivating in some parts of their lands for the next planting season and the rest will be still waiting for market response and confirmation. Farmers which located in the area as the producer of onion sold their product to middlemen or fences. The middlemen sell the onion to the traders across the regions or to the wholesalers both from the local area and outside the area.